Development and Characterization of Self-nano-emulsifying Drug-delivery System for Oral Delivery of Verapamil - Panga, Shyam (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: The present study deals with the development and characterization of self-nano-emulsifying drugdelivery system (SNEDDS) to improve the oral bioavailability of water-insoluble biopharmaceutical classification system Class II drug verapamil. The objectives of the study are to develop SNEDDS of verapamil and to characterize for particle size, self-nano-emulsification, and dissolution enhancement. Solubility of verapamil was determined in various oils, surfactants, and cosurfactants. Materials and Methods: Captex 355 was selected as an oil phase, acrysol K140 as surfactant, and PEG400 as cosurfactant due to their higher solubilization effect. Results: Various formulations were prepared by simple mixing followed by vortexing. From studies, the optimized SNEDDS formulation was composed of verapamil (9.13% w/w), captex 355 (23.41% w/w), acrysol K140 (51.62% w/w), and PEG 400 (11.58% w/w). The selected SNEDDS could be self-emulsified without precipitation on simple mixing. The mean particle size of the SNEDDS was 148.7 nm and percent drug content was 99.66. The in vitro dissolution of verapamil from SNEDDS was found to be significantly higher (95.4 ± 2.07) in comparison to the marketed tablet (64.8 ± 1.36) and pure drug (52.5 ± 1.65) in 0.1 N HCl as dissolution medium. Conclusion: The results indicate that SNEDDS of verapamil, due to its nanosized, has potential to enhance the absorption of drug due to its higher dissolution.